Knowledge of Men and Women about Infertility Risk Factors - Amirreza Talaiekhozani; Sanaz Alaee; Gholam Reza Ziaei; Masoud Mir; Mehdi Yazdan; Mahmood Sadeghi Ataabadi (Iranian Journal of Health, Safety and Environment, 2016)
With technological developments, creation of new industries and changing lifestyles, infertility risk factors (IRF) increased. Therefore creation of suitable solutions in society is crucial for the prevention of infertility. Since prevention of infertility in a society is directly related to awareness about infertility, in the present study the awareness of people about infertility risk factors was assessed. In this study, a survey questionnaire containing 24 factors related to IRF was developed and 170 persons (62 men and 108 women) from Fooladshahr, Najafabad and Mobarakeh participated and data were extracted from these questionnaires and were statistically analyzed. Our study showed that average infertility awareness for men and women is 38% and 49% respectively. Also overall awareness was 44%. Also results showed that women's awareness about mobile radiation and fast foods is significantly higher than men. On the other hand men have significantly higher awareness about adverse effects of chlorine in swimming pool on fertility. Higher women awareness may be related to their higher sensitivity for fertility. Also, generally a higher level of awareness was observed relating to mobile, air pollution, stress, fast foods, smoking and alcohol. Women have a higher level of awareness about infertility risk factors. Higher awareness about some IRFs may be results from widespread media coverage.